Past and present of the nematode radopholus similis (cobb) thorne with emphasis on musa: a review (2011)
This review presents a historical background on different aspects of the nematode Radopholus similis (Cobb) Thorne, an important pathogen of Musa, black pepper and anthurium. It examines the history of its discovery and its name, new approaches to its taxonomy and its genome, and the process of dissemination and pathogenic variability. Finally, it documents the evolution of the control measures in banana, from chemical control to bio-protection and managing the habitat of the pathogen.